"Deep" vertical Mohs and closure with a tumor-free flap for dermatofibrosarcoma protuberans: A case report. (April 2019) - John, Ann M; Francisco, Gina; Srivastava, Radhika; Bhatti, Hamza; Rao, Babar K
Dermatofibrosarcoma protuberans is an uncommon low-grade malignant tumor that can invade locally and rarely metastasize. Dermatofibrosarcoma protuberans has a high rate of local recurrence due to incomplete excision, especially in deep tissues. Morbidity is often related to multiple local recurrences and removal of excessive tissue with large, complex repairs. We present a case of incompletely excised dermatofibrosarcoma protuberans after initial wide local excision. We subsequently employed a "deep" vertical Mohs micrographic surgical technique to remove the remaining tumor while creating a flap with the tumor-free superficial portion to preserve tissue and avoid a complicated repair. The patient is tumor-free for 7 years.